Penelitian Produk: Inovasi Pembuatan Cheese Cake Menggunakan Bahan Kacang Panjang Sebagai Pengganti Tepung Terigu - Nonot Yuliantoro (Akademi Pariwisata Bunda Mulia, 2019)
ABSTRACT Making cheesecake using long bean is one of the latest innovations in making cheese cake that has never been seen before. Cheesecake generally use flour, this study aims at how long bean can be used as a component of chiffon cheesecake by drying and processing into vegetabel flour. This research was conducted to find out whether vegetabel flour can affect the texture, taste, aroma and color of cheesecake. The purpose of long bean as a substitute for wheat flour is for consumption for the general public, especially for those who cannot consume gluten and make an alternative for people who do not like vegetabels. In this study, we have conducted several vegetabel group studies ranging from vegetabel, leaf, stem, flower and fruit groups. Then found the right vegetabel group to be made as a component of cheesecake, namely fruit vegetabels. In addition, modifications are also made to the recipe, especially on the amount of vegetabel flour. Excessive amounts will greatly affect the taste, texture, and aroma of the cheesecake. This study uses the homemade method. Homemade, which is meant by itself, is the making of using equipment that is few and can be made by anyone with the right technique.Keyword: Cheese cake, long bean, homemade ABSTRAK Pembuatan cheesecake dengan menggunakan kacang panjang merupakan salah satu inovasi terbaru pembuatan cheesecake. Chiffon Cheesecake pada umumnya menggunakan tepung terigu, Penelitian ini menggunakan sayuran kacang panjang sebagai bahan pengganti tepung terigu dengan cara mengeringkan kacang panjang dan di olah menjadi tepung sayuran. Tujuan penelitian untuk mengetahui apakah tepung sayuran bisa mempengaruhi tekstur, rasa, aroma dan warna pada cheesecake. Pemilihan Sayuran sebagai pengganti tepung terigu adalah alternative pengganti bagi mereka yang tidak bisa mengkonsumsi gluten serta menjadikan alternatif bagi orang-orang yang tidak menyukai sayuran. Di dalam penelitian ini, dilakukan percobaan pembuatan cheesecake dengan bahan berbagai golongan sayuran. Kemudian ditemukan golongan sayuran yang tepat untuk di jadikan komponen cheesecake yaitu sayuran buah. Selain itu, dilakukan juga modifikasi pada resep terutama pada jumlah tepung sayuran. Jumlah yang berlebihan akan sangat mempengaruhi rasa, tekstur, dan aroma pada cheesecake. Dalam melakukan uji coba produk dilakukan dengan cara homemade.Kata kunci: Cheese Cake, kacang panjang, homemade.